Thinking the limits of the body - Cohen, Jeffrey Jerome; Weiss, Gail, 1959- (Albany : State University of New York Press, 2003)
This collection maps the very best efforts to think the body at its limits. Because the body encompasses communities (social and political bodies), territories (geographical bodies), and historical texts and ideas (a body of literature, a body of work), Cohen and Weiss seek trans-disciplinary points of resonance and divergence to examine how disciplinary metaphors materialize specific bodies, and where these bodies break down and/or refuse prescribed paths. Whereas postmodern theorizations of the body often neglect its corporeality in favor of its cultural construction, this book demonstrates the inseparability of textuality, materiality, and history in any discussion of the body.
Introduction : Bodies at the limit / Jeffrey Jerome Cohen and Gail Weiss -- Histories of the present and future : feminism, power, bodies / Elizabeth Grosz -- The body as a narrative horizon / Gail Weiss -- Cutups in beauty school / Linda S. Kauffman -- Deep skin / William A. Cohen -- Ontological crisis and double narration in African American fiction : reconstructing Our nig / Laura Doyle -- Parallaxes : cannibalism and self-embodiment; or, the Calvinist reading of Tupi a-theology / Sara Castro-Klarén -- Making freaks : visual rhetorics and the spectacle of Julia Pastrana / Rosemarie Garland-Thomson -- Critical investments : AIDS, Christopher Reeve, and queer/disability studies / Robert McRuer -- The inhuman circuit / Jeffrey Jerome Cohen -- Mourning the autonomous body / Debra B. Bergoffen.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Human body -- Social aspects; Human body (Philosophy); Corps humain -- Aspect social; Corps humain (Philosophie); SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Human body (Philosophy); Human body -- Social aspects